Wewenang Presiden dalam Penyelenggaraan Negara Terkait Perpindahan Ibu Kota Negara - Zuliandri, Muhammad Faishal; Isharyanto, Isharyanto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2021)
ABSTRACTThe President has stated his intention to move the nation’s capital city (capital city or state capital) from Jakarta to Kalimantan. The idea arises because the president wants to implement the equitable distribution of national development. Jakarta is, by law, the legal capital city of Indonesia in accordance with Law No. 29 of 2007. However, regulations regarding the relocation of state capital have not been clearly regulated in Indonesian law. In connection with the plan, problems arose regarding the presidential authority to relocate the state capital. The problem in this study emphasizes on: how is the presidential authority in moving the state capital? Why should the capital move? The research method used is normative legal research that is qualitative in nature. The purpose of this research is to find out whether the relocation of the state capital by the president is in accordance with the applicable legal rules and to know the relocation factors of the state capital. The theoretical benefit of this research is for the development of science, especially in respect of the presidential authority. While the practical benefits of this research are to serve as the consideration of the stakeholders in the lawmaking process related to the relocation of the state capital in Indonesia. Keywords : the authority of the president; state capital; relocation of the state capital.